Child Neglect and Its Psychological Consequences on Children: A Case Study of Anppcan Kampala, Uganda - Mianah Keinembabazi (Uganda Christian University, 2025)
In contrast to physical or sexual abuse, child neglect is a pervasive and subtle kind of maltreatment that is sometimes overlooked because of its less obvious character. Neglect, no matter how slight, can have serious and long-lasting psychological effects on kids. Neglect is distinguished from abuse by the absence of damaging behaviors; that is, when caregivers fail to offer necessary care, emotional support, and protection. A child's emotional and psychological development may be hampered by this lack of care, which could have a variety of negative effects. Studies have consistently demonstrated that children who are neglected are more likely to experience mental health problems such sadness, anxiety, and posttraumatic stress disorder (PTSD) (Tingberg & Nilsson, 2020). Attachment difficulties, trouble establishing connections, and behavioral issues like violence or social disengagement may also be present. Moreover, the consequences of neglect may persist into adulthood, impacting an individual's capacity to uphold sound relationships, excel in their profession, and attain a general sense of contentment with life. Even though neglect has a significant negative effect on a child's mental health, it is still one of the areas of child abuse that receives the least amount of research. A substantial knowledge vacuum exists on the entire range of psychological damage resulting from neglect, as the majority of research on child abuse concentrates on more obvious types of maltreatment (Tingberg & Nilsson, 2020). The fact that neglect is one of the most prevalent types of child abuse that are reported worldwide makes this lack of care very alarming. Given the prevalence of child neglect and its potentially disastrous consequences, a thorough investigation into the psychological effects of neglect, taking into account various forms of neglect, and examining moderating factors that may influence these outcomes is desperately needed. In addition to addressing a major vacuum in the literature, this research is crucial for informing the creation of focused treatments and support networks that will assist neglected children and lessen the long-term effects of their mistreatment.
THESIS